Porous Silicon Sensing Membrane Electrode on Extended Gate Field Effect Transistor for pH Sensor - Narin Atiwongsangthong; Atthawit Ausama; Seangrawee Buakaew (My University, 2023)
In this paper, we used porous silicon as sensing membrane electrode which were formed by using anodization etching process at room temperature. Porous silicon sensing membrane electrode will be combined working with commercial N-MOSFET which used as the extended gate field effect transistor (PS-EGFET) for pH sensor. P-type silicon wafer was used as material substrate for prepare porous silicon sensing membrane electrode. Anodization parameters, the current density of 10 mA/cm2, with 48% hydrofluoric acid concentration and etching time of 10 minutes. The pH sensing of porous silicon EGFET were measured in pH value of 4, 7 and 10, respectively. From experiment, the porous silicon EGFET were exhibited high pH sensitivity on current mode in relationship between the drain current with pH value was $0.2929\ \mu\mathrm{A}^{1/2}/\text{pH}$, corresponding to the linearity of 99.72%. And, pH sensitivity on voltage mode in relationship between reference voltage with pH value was 34.8 mV/pH, corresponding to the linearity of 99.78%. The experiment results showed that the porous silicon was suitable sensing membrane material for pH sensor.
Keywords: Silicon Nanostructures and Photoluminescence; Nanowire Synthesis and Applications; Semiconductor materials and devices